The analgesic and anti-inflammatory effect of lawsone isolated from Lawsonia inermis - Talab, Tayseer Ali; Alfuraiji, Narjes; Al-Snafi, Ali Esmail (ScienceRise: Pharmaceutical Science, 2022)
This study aimed to assess the analgesic and anti-inflammatory effects of lawsone isolated from henna leaves (Lawsonia inermis). Methods: A total of 120 healthy adult mice (weighing about 25±5 g) were included in this study. Sixty mice out of the total were used to determine LD50, 30 mice to determine the anti-inflammatory test, and the remaining (30 mice) were used for an analgesic test. The hot plate was used to determine the analgesic effect, while the anti-inflammatory effect was determined by the ability of the compound to minimize the inflammation and edema caused by the injection of carrageenan. Results: Lawsone was isolated from Lawsonia inermis. A Stuart SMP10 digital melting point apparatus was used for measuring all melting points. Infrared spectrometer FT-IR 400D was used for measuring/recording IR spectra (KBr) which the frequency of absorption was represented as cm−1. For 1H-NMR spectrum recording, a Bruk-spectrophotometer of 400 MHz was used with internal TMS standard, with deuterated Ś 2.51 ppm for acetone-d6, remained solvent signals as well as 13C.NMR was used. TLC was utilized as adsorbent, UV light, or iodine-completed visualization to verify compounds' purities. The LD50 of the oral lawsone was 96 mg/kg, and the highest dosage that did not kill any of the experimental animals was 80 mg/kg, which was used to investigate lawsone's analgesic and anti-inflammatory effects. Lawsone and aspirin possessed an analgesic effect compared to the control group (p<0.0001 and p<0.001, respectively); however, lawsone induced a potent analgesic effect compared to aspirin (p<0.1). In contrast, Lawsone and aspirin exerted an anti-inflammatory effect (p<0.05) compared to the control group and were equipotent in carrageenan-induced hind paw edema. Conclusion: It is concluded that lawsone possesses analgesic and anti-inflammatory effects, which endorse the practical medical importance of Lawsonia inermis. The latter is widely used traditionally for these purposes own to its cost-effectiveness and safety; however, further studies are required to determine the systemic safety of lawsone